The DNA of constitutional justice in Latin America : politics, governance, and judicial design / Daniel M. Brinks, Abby Blass. - Brinks, Daniel M., 1961-; Blass, Abby (Comparative constitutional law and policy., 2018)
In recent times there has been a dramatic change in the nature and scope of constitutional justice systems in the global south. New or reformed constitutions have proliferated, protecting social, economic, and political rights. While constitutional courts in Latin America have traditionally been used as ways to limit power and preserve the status quo, the evidence shows that they are evolving into a functioning part of contemporary politics and a central component of a system of constitutional justice. This book lays bare the political roots of this transformation, outlining a new way to understand judicial design and the very purpose of constitutional justice. Authors Daniel M. Brinks and Abby Blass use case studies drawn from nineteen Latin American countries over forty years to reveal the ideas behind the new systems of constitutional justice. They show how constitutional designers entrust their hopes and fears to dynamic governance systems, in hopes of directing the development of constitutional meaning over time.